Development of a Swirl‐Induced Rotating Glow Discharge Reactor for CO2 Conversion: Fluid Dynamics and Discharge Dynamics Studies. Issue 12 (19th October 2020) - Raja, Bharathi; Sarathi, Ramanujam; Vinu, Ravikrishnan
Abstract : Herein, CO2 conversion is conducted in a newly developed swirl flow–induced rotating glow discharge reactor. The swirl injector is designed to produce forward vortex by eight inclined guided vanes. A glow‐type rotating discharge is formed between two electrodes of constant height. The discharge and fluid dynamics studies reveal that the magnitude of tangential velocity and secondary vortex formation affects the rotational frequency of the discharge. It is also found that the anchoring point of the plasma column root is greatly influenced by the increased pressure gradient, especially in the turbulent regime. The conversion of CO2 as a function of flow rate is found to increase in the laminar regime and decrease in the turbulent regime. With increasing specific energy input from 0.25 to 3.4 kJ L −1, there is a rise in conversion from 1.2% to 4.6%, which indicates the high residence time and high energy deposition to lesser number of CO2 molecules. Higher energy efficiencies (54.9–63.7%) at turbulent flow rates show that this swirl design enhances the distribution of electron energy to incoming fresh molecules by formation of circulation zones and turbulence. Abstract : A novel swirl flow–induced rotating glow discharge reactor for CO2 conversion is developed. The rotational frequency of the plasma column is controlled by the tangential velocity of the peripheral vortex in the laminar regime. Plasma column shifting to the central hub and increased turbulence enhance the energy efficiency of the process.